Rate of tooth movement and dentoskeletal effects of rapid canine retraction by dentoalveolar distraction osteogenesis: A prospective study - KURT, GÖKMEN; KURT, GÖKMEN; İŞERİ, MUSTAFA HALUK; KİŞNİŞCİ, REHA ŞÜKRÜ; ÖZKAYNAK, Özkan (My University, 2017)
Introduction: The purpose of this study was to test the null hypothesis that duration of orthodontic treatment can be significantly reduced by accelerating canine retraction using dentoalveolar distraction (DAD). Methods: Thirty-six maxillary canines of 19 patients comprised the DAD group, and 28 canines of 14 patients were included in the distalization group (DG). The initial mean ages were 15.8 +/- 1.96 years for the DAD group and 16.02 +/- 2.8 years for the DG. A custom-made, rigid, tooth-borne intraoral distraction device was used for the DAD group, and intraoral elastics were applied for canine distalization in the DG. Six skeletal and 11 dental variables were measured for the cephalometric evaluation. Results: Canine retraction was 7.9 +/- 1.49 mm in 11.8 +/- 1.3 days and canine distal tipping was 11.48 degrees +/- 4.37 degrees after DAD; the canines were distalized 5.29 +/- 2.01 mm and tipped 13.64 degrees +/- 9.54 degrees in 200 +/- 57 days in the DG. The rates of posterior canine movement were 0.67 +/- 0.14 mm per day after DAD and 0.03 +/- 0.01 mm per day in the DG. No significant first molar anchorage loss was observed after DAD, although the DG showed some vertical and sagittal first molar movement. Conclusions: We failed to reject the null hypothesis. DAD can reduce the duration of orthodontic treatment time by accelerating canine retraction in extraction patients without undesirable side effects.